2020
DOI: 10.34172/japid.2020.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gingival biotype on orthodontic treatment-induced periodontal complications: A systematic review

Abstract: Background. It is crucial to maintain periodontal health in patients undergoing orthodontic treatment. Biotype is a critical factor to be considered in this regard. This systematic review investigated the scientific evidence on the relationship between gingival biotype and marginal periodontal alterations induced by orthodontic interventions. Methods. An electronic search was conducted for pertinent studies in three databases: PubMed, Scopus, and Cochrane up to August 1, 2019 based on a detailed protocol acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…31 In the case of lingual movement, periodontal treatment can be postponed until after the completion of orthodontic movement. 2,6 Periodontal intervention during orthodontic therapy is justified in the case of progressive recessions in patients with KTW > 2 mm. 6 A recent systematic review reported a mean GT gain of 0.81 mm using collagen matrixes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…31 In the case of lingual movement, periodontal treatment can be postponed until after the completion of orthodontic movement. 2,6 Periodontal intervention during orthodontic therapy is justified in the case of progressive recessions in patients with KTW > 2 mm. 6 A recent systematic review reported a mean GT gain of 0.81 mm using collagen matrixes.…”
Section: Discussionmentioning
confidence: 99%
“…2,6 Periodontal intervention during orthodontic therapy is justified in the case of progressive recessions in patients with KTW > 2 mm. 6 A recent systematic review reported a mean GT gain of 0.81 mm using collagen matrixes. 32 As the mean increase in GT in this study was 2.02 ± 0.39 mm, it seems that the proposed method may be an efficient technique in soft tissue phenotype modification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gingival biotype of lower anteriors was thin for almost 27 participants and thick for 13 participants which after orthodontic treatment showed that five participants had their gingival biotype reversed to normal from a thin biotype and the others did not have any difference at T1 (Table 1). A systematic review by Amid et al 17 studied the effects of orthodontic treatment on the periodontium and concluded that orthodontic treatment did have some mild detrimental effects on the periodontium especially in patients with thin gingival biotype. From Figure 3a–c, it is observed that the loss of gingival keratinization and thin gingival biotype with respect to the traumatized left central incisor has not reversed at the mid as well as post-orthodontic treatment (T1).…”
Section: Discussionmentioning
confidence: 99%